2022
DOI: 10.3390/molecules27123863
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Phytochemicals and Anti-Cancer Potential of the Members of Fabaceae Family: A Comprehensive Review

Abstract: Cancer is the second-ranked disease and a cause of death for millions of people around the world despite many kinds of available treatments. Phytochemicals are considered a vital source of cancer-inhibiting drugs and utilize specific mechanisms including carcinogen inactivation, the induction of cell cycle arrest, anti-oxidant stress, apoptosis, and regulation of the immune system. Family Fabaceae is the second most diverse family in the plant kingdom, and species of the family are widely distributed across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 158 publications
0
24
0
Order By: Relevance
“…Polyphenols, as natural antioxidants, inhibit the oxidation of lipids, proteins and nucleic acids, thus preventing the initiation of oxidative chain reactions. These compounds can significantly reduce the risk and incidence of cancer by scavenging unstable molecules that could initiate carcinogenicity [ 59 , 60 , 61 , 62 ]. In vitro plant cell cultures could serve as a good source of PCs with different cytotoxic activity towards normal and cancer cells [ 51 ].…”
Section: New Sources Of Phenolic Compoundsmentioning
confidence: 99%
“…Polyphenols, as natural antioxidants, inhibit the oxidation of lipids, proteins and nucleic acids, thus preventing the initiation of oxidative chain reactions. These compounds can significantly reduce the risk and incidence of cancer by scavenging unstable molecules that could initiate carcinogenicity [ 59 , 60 , 61 , 62 ]. In vitro plant cell cultures could serve as a good source of PCs with different cytotoxic activity towards normal and cancer cells [ 51 ].…”
Section: New Sources Of Phenolic Compoundsmentioning
confidence: 99%
“…Meanwhile, the ability of flavonoids to reduce free radicals depends on the free OH group, especially the 3-OH group. Previous studies reported that phenolic compounds have anti-inflammatory (Brezani et al 2018), anticarcinogenic (Usman et al 2022), and anti-atherogenic activities (Othman et al 2020). Kumar and Pandey (2013) revealed that flavonoid compounds have antiinflammatory, anti-cancer, anti-coronary heart disease, and hepatoprotective activities.…”
Section: Phenolics and Flavonoids Contentsmentioning
confidence: 99%
“…The Fabaceae family is the second most widespread family in the plant kingdom, with species found worldwide. The Fabaceae family contains a high concentration of phytochemicals (flavonoids, phenolic acids, saponins, alkaloids, lectins, and carotenoids) which have a variety of health benefits, notably anti-cancer activities [13]. Fabaceae as Fava beans restrictions for people with glucose-6-phosphate dehydrogenase deficiency are historically known to provoke severe acute hemolytic anemia in individuals with G6PD deficiency [14].…”
Section: Introductionmentioning
confidence: 99%